Strengthening Religious Moderation to Counter Radicalism at IAIN Surakarta - Moh Ashif Fuadi; Fuad Hasyim; Muhammad Nur Kholis; Abraham Zakky Zulhazmi; Rustam Ibrahim (AL-TAHRIR, 2021)
Abstract: Religious moderation discourse in Indonesia has recently attracted the attention of many parties, especially academics. Moderation means in the middle-center, neither to the right nor the left. In religious issues, religious moderation does not involve radicalism, fundamentalism, and liberalism. It is congruous for religious higher education to be a laboratory of religious moderation. It embeds national ideas, critical thinking constructs, multiculturalism values cultivation, and the peaceful delivery of spiritual messages. This research discusses the implementation of religious moderation at IAIN Surakarta. The internalization of moderation values to students is channeled through Bilik Moderasi Islam dan Adab (BIMA) of the Faculty of Adab and Language. This study employed descriptive qualitative methods with progress reports. It concluded the existence of several channels of moderation at the institutional level. BIMA became one of the pioneers of the religious moderation movement in the faculty. The prevention of radicalism was done in some ways. They establish moderation insight courses, conduct monthly studies on moderation, and create moderation digital creative content. Not only that but also BIMA certificates became the requirement of munaqosah. Besides, the progress report of the moderation index measurement showed the effect of BIMA coaching on the increase in the student moderation index. Based on the survey, most students also suggested maintaining the religious moderation education.الملخص: استحوذ الحديث عن الاعتدال الديني في إندونيسيا مؤخرا على اهتمام العديد من الأطراف والأحزاب، خاصة  الأكاديميين. تحتوي كلمة الاعتدال على معنى الوسط، ولا يتعدى إلى اليمين أو إلى اليسار. عندما يرتبط الأمر بالقضايا الدينية، فإن ممارسة الاعتدال الديني هي السلوك والتصرف الذي لا يتبع التطرف والأصولية والليبرالية. الجامعة الإسلامية مناسبة جدا لتكون مختبرا للاعتدال الديني. فالجامعة الإسلامية هي المكان تصدر ة تنمو منه  الأفكار الوطنية، وبناء التفكير النقدي، وتنمية قيم التعددية الثقافية، والتسليم السلمي للرسائل الدينية. يناقش هذا البحث تنفيذ الاعتدال الديني في جامعة سوراكارتا الإسلامية الحكومية. من خلال وحدة Bilik Islam Moderasi dan Adab (IMAB) التابع لكلية الآداب واللغات، يتم توجيه استيعاب قيم الاعتدال للطلاب. مع أساليب وصفية نوعية مع تقارير مرحلية،أدى هذا البحث إلى الانتهاء  من عدة قنوات للاعتدال على المستوى المؤسسي وأصبح BIMA  أحد رواد  حركة الاعتدال الديني في الكلية. أصبحت الجهود المبذولة لمنع التطرف من خلال إنشاء دورات رؤية الاعتدال ، والدراسات الشهرية تحت عنوان الاعتدال ، وإنشاء  منتجات المحتوى الإبداعي الرقمي الاعتدال  وشهادات IMAB شرطا لجلسات مناقشة البحث العلمي.  ويبين التقرير المرحلي لقياس مؤشر الاعتدال تأثير تدريب IMAB على الزيادة في مؤشر اعتدال الطلاب، واستنادا إلى مسح غالبية الطلاب الذين يرغبون في الحفاظ على تعليم الاعتدال الديني.Abstrak: Diskursus moderasi beragama di Indonesia belakangan ini menyita perhatian banyak pihak khususnya kalangan akademisi. Kata moderasi mengandung makna tengah-tengah, tidak ekstrem ke kanan atau ke kiri. Jika dikaitkan dengan persoalan agama, praktik moderasi beragama itu bersikap dan berperilaku yang tidak mengikuti radikalisme, fundamentalisme dan liberalisme. Pendidikan Tinggi Keagamaan sangat tepat menjadi laboratorium moderasi beragama. Perguruan tinggi keagamaan sejatinya menjadi lahan tersemainya gagasan kebangsaan, konstruk pemikiran kritis, penanaman nilai-nilai multikulturalisme dan penyampaian pesan agama yang damai. Penelitian ini membahas tentang implementasi moderasi beragama di IAIN Surakarta. Melalui unit Bilik Moderasi Islam dan Adab (BIMA) Fakultas Adab dan Bahasa, maka internalisasi nilai-nilai moderasi kepada mahasiswa disalurkan. Dengan metode kualitatif deskriptif dengan progress report, penelitian ini menghasilkan kesimpulan adanya beberapa saluran moderasi di tingkat institusi dan BIMA menjadi salah satu pelopor gerakan moderasi beragama di fakultas. Upaya pencegahan radikalisme dilakukannya melalui   penetapan mata kuliah wawasan moderasi, kajian bulanan bertemakan moderasi, pembuatan produk konten kreatif digital moderasi dan sertifikat BIMA menjadi syarat untuk sidang munaqosah. Adapun progress report pengukuran indeks moderasi menunjukkan aadanya pengaruh pembinaan BIMA terhadap kenaikan indeks moderasi mahasiswa dan berdasar survei mayoritas mahasiswa menginginkan edukasi moderasi beragama terus dipertahankan.